Coronavirus disease 2019 pandemic and pregnancy and neonatal outcomes in general population: A living systematic review and meta‐analysis (updated Aug 14, 2021) - Jie Yang; Rohan D’Souza; Ashraf Kharrat; Deshayne B. Fell; John W. Snelgrove; Kellie E. Murphy; Prakesh S. Shah (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Conflicting reports of increases and decreases in rates of preterm birth (PTB) and stillbirth in the general population during the coronavirus disease 2019 (COVID‐19) pandemic have surfaced. The objective of our study was to conduct a living systematic review and meta‐analyses of studies reporting pregnancy and neonatal outcomes by comparing the pandemic and pre‐pandemic periods. Material and methods We searched PubMed and Embase databases, reference lists of articles published up until August 14, 2021 and included English language studies that compared outcomes between the COVID‐19 pandemic time period and the pre‐pandemic time periods. Risk of bias was assessed using the Newcastle–Ottawa scale. We conducted random‐effects meta‐analysis using the inverse variance method. Results Forty‐five studies with low‐to‐moderate risk of bias, reporting on 1 843 665 pregnancies during the pandemic period and 23 564 552 pregnancies during the pre‐pandemic period, were included. There was significant reduction in unadjusted estimates of PTB (35 studies, unadjusted odds ratio [uaOR] 0.95, 95% CI 0.92–0.98), but not in adjusted estimates (six studies, adjusted OR [aOR] 0.95, 95% CI 0.80–1.13). This reduction was noted in studies from single centers/health areas (25 studies, uaOR 0.90, 95% CI 0.86–0.96) but not in regional/national studies (10 studies, uaOR 0.99, 95% CI 0.95–1.02). There was reduction in spontaneous PTB (six studies, uaOR 0.89, 95% CI 0.81–0.96) and induced PTB (five studies, uaOR 0.89, 95% CI 0.81–0.97). There was no difference in the odds of stillbirth between the pandemic and pre‐pandemic time periods (24 studies, uaOR 1.11, 95% CI 0.97–1.26 and four studies, aOR 1.06, 95% CI 0.81–1.38). There was an increase in mean birthweight during the pandemic period compared with the pre‐pandemic period (six studies, mean difference 17 g, 95% CI 7–28 g). The odds of maternal mortality were increased (four studies, uaOR 1.15, 95% CI 1.05–1.26); however, only unadjusted estimates were available and the result was mostly influenced by one study from Mexico. There was significant publication bias for the outcome of PTB. Conclusions The COVID‐19 pandemic may be associated with a reduction in PTB; however, referral bias cannot be excluded. There was no statistically significant difference in stillbirth between pandemic and pre‐pandemic periods.